A low apparent density biodegradable film material and a method for preparing the same
Patent Information
- Application Number
- CN202410320122.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-03-20
AI Technical Summary
[0002]生物降解塑料PBAT有着较好的延展性和可加工性,还具有优良的生物降解性,可应用于商超购物袋、奶茶袋、快递包装袋、农用地膜等领域,有很好的发展前景,但是PBAT包装薄膜价格相对于传统的PE薄膜高50%以上,需要降低成本,才能实现行业快速发展
[0044](1)本发明对PBAT进行结构设计,首先通过含有活性基团的封端剂对PBAT树脂进行封端,然后引入酸类单体和丙烯酸酯类单体进行共聚,改变分子链段的规整度,提高材料的力学性能。
Smart Images

Figure BDA0004750288320000021 
Figure BDA0004750288320000071 
Figure BDA0004750288320000081
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials, specifically relating to a low apparent density biodegradable thin film material and its preparation method. Background Technology
[0002] Biodegradable plastic PBAT has good ductility and processability, as well as excellent biodegradability, making it suitable for applications such as supermarket shopping bags, milk tea bags, express delivery packaging bags, and agricultural mulch films, showing great development potential. However, PBAT packaging film is more than 50% more expensive than traditional PE film, requiring cost reduction for rapid industry development. While reducing material costs can be achieved by lowering the film's apparent density, this significantly reduces its mechanical properties, failing to meet application requirements.
[0003] CN 110283438 A discloses a base resin for blown biodegradable films and blown biodegradable films. The method uses poly-L-lactic acid and adipic acid-terephthalic acid-butanediol copolymer as the matrix, and introduces diol oligomers and reactive compatibilizers into this system. A modified product with a partially cross-linked structure is formed in situ through reactive blending. This modified product can be blended with foaming particles in a blown film machine to form a film. This method reduces the apparent density of the film while ensuring its strength and toughness, but it requires the addition of a foaming agent, and the foaming process is difficult to control.
[0004] Therefore, it is necessary to provide a novel PBAT membrane material to solve the above problems. Summary of the Invention
[0005] To address the aforementioned problems in the existing technology, the present invention aims to provide a low apparent density biodegradable thin film material and its preparation method, which can effectively reduce its apparent density while ensuring the film strength and elongation.
[0006] In the process of researching the preparation of biodegradable thin film materials using PBAT, this invention unexpectedly discovered that by first end-capping PBAT resin with an end-capping agent containing active groups, and then introducing acidic monomers and acrylate monomers to modify the PBAT resin, the regularity of the molecular chain segments can be improved, thereby enhancing the mechanical properties of the material. Furthermore, within the raw material ratio range used in this invention, the acidic monomers can control the end-carboxyl group content of the modified PBAT resin within a suitable range, promoting the reaction between the PBAT resin and calcium carbonate at high temperatures, forming tiny pores on the surface. This ensures the mechanical properties of the film while resulting in a lower apparent density and better market application prospects.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] This invention provides a low apparent density biodegradable thin film material, comprising the following components, in parts by weight:
[0009]
[0010] The modified PBAT resin is prepared by end-capping PBAT resin with an end-capping agent and then introducing acid monomers and acrylate monomers.
[0011] In this invention, the source of the PBAT resin is not particularly important, but it is preferred to use PBAT resin with a melt index of 2-8 g / 10 min (190°C, 2.16 kg), such as 2 g / 10 min, 3 g / 10 min, 4 g / 10 min, 5 g / 10 min, 6 g / 10 min, 7 g / 10 min, 8 g / 10 min, and preferably 4-7 g / 10 min (190°C, 2.16 kg).
[0012] The PBAT resin has a weight-average molecular weight of 90,000 to 150,000, for example, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, or 150,000, preferably 100,000 to 140,000.
[0013] The PBAT resin has a terminal carboxyl group content of 5-25 mol / t, for example 5, 8, 10, 13, 18, 20, 23, 25 mol / t, preferably 10-24 mol / t.
[0014] In this invention, the capping agent is a capping agent containing an active group, wherein the active group is selected from epoxy groups and / or oxazoline groups;
[0015] Preferably, the end-capping agent is selected from vinyl end-capping agents, more preferably one or more of vinyl oxazoline end-capping agents and vinyl epoxy end-capping agents, and more preferably one or more of 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and glycidyl methacrylate.
[0016] In this invention, the acid monomers are selected from one or more of acid anhydride monomers and carboxylic acid monomers, preferably one or more of maleic anhydride, methacrylic acid, and 2,3-diphenylmaleic anhydride.
[0017] In this invention, the acrylate monomer is one or more of methyl methacrylate, ethyl methacrylate, and methyl 2-(hydroxymethyl)acrylate.
[0018] In this invention, the modified PBAT resin has an end carboxyl group content (i.e., acid value) of 50-150 mol / t, for example, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150 mol / t. The end carboxyl group content can be controlled within a suitable range by using acid monomers, so that it has a low apparent density of film.
[0019] In this invention, the calcium carbonate has a mesh size of 800-10000 mesh, such as 800, 1000, 3000, 5000, 7000, 9000, or 10000 mesh, preferably 2000-8000 mesh.
[0020] In this invention, the coupling agent is selected from one or more of silane coupling agents and phthalate coupling agents, preferably one or more of γ-aminopropyltriethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-(methacryloyloxy)propyltrimethoxysilane.
[0021] In this invention, the lubricant is a conventional additive in the field, selected from one or more of erucamide, oleamide, ethylene bis-stearamide, etc.
[0022] In this invention, modified PBAT resin prepared by any method can be used. Unless otherwise specified, the modification method can refer to the prior art, such as conventional end-capping process, polymerization process, blending modification process, etc. Preferably, a blending extrusion device is used. In the melt extrusion process, PBAT resin and end-capping agent are mixed and reacted to obtain end-capped PBAT, and then polymerized with acid monomers and acrylate monomers to obtain modified PBAT resin.
[0023] Specifically, the modified PBAT resin of the present invention is preferably prepared by the following method, including the following steps:
[0024] (1) Mix PBAT resin and end-capping agent thoroughly, add to an extruder, heat to carry out end-capping reaction, melt extrusion, cool, pelletize, dry to obtain end-capped PBAT;
[0025] (2) The end-capped PBAT, acid monomers, acrylate monomers and initiator are thoroughly mixed and added to an extruder. The mixture is heated to carry out the polymerization reaction. After melt extrusion, cooling, pelletizing and drying, the modified PBAT resin is obtained.
[0026] In this invention, the mass ratio of PBAT resin to end-capping agent in step (1) is 100:(0.1-2), for example 100:0.1, 100:0.5, 100:1, 100:1.5, 100:2, preferably 100:(0.3-1.8).
[0027] In this invention, the initiator in step (2) is a conventional additive in the field, selected from one or more of dicumyl peroxide, benzoyl peroxide, and methyl ethyl ketone peroxide, preferably dicumyl peroxide.
[0028] In this invention, the mass ratio of the end-capped PBAT to the acid monomer, acrylate monomer, and initiator in step (2) is 100:(0.1-2):(1-4):(0.1-1.2), for example 100:0.1:1:0.1, 100:0.4:1.5:0.3, 100:0.7:2:0.5, 100:1:2.5:0.7, 100:1.3:3:0.9, 100:1.6:3.5:1, 100:2:4:1.2, preferably 100:(0.3-1.8):(1.5-3.5):(0.2-1).
[0029] In this invention, the end-capping reaction in step (1) involves controlling the extruder temperature to be 140-180°C, for example, 140, 145, 150, 155, 160, 165, 170, 175, or 180°C, preferably 145-175°C;
[0030] Preferably, the screw speed of the extruder is 100-700 rpm, for example 100, 200, 300, 400, 500, 600, or 700 rpm, and more preferably 200-600 rpm.
[0031] In this invention, the polymerization reaction in step (2) is controlled at an extruder temperature of 120-150°C, for example 120, 125, 130, 135, 140, 150°C, preferably 125-145°C;
[0032] Preferably, the screw speed of the extruder is 50-500 rpm, for example 50, 100, 200, 300, 400, 500 rpm, and more preferably 100-400 rpm.
[0033] In this invention, the end-capping reaction in step (1) and the polymerization reaction in step (2) involve extruder temperature, which is the reaction temperature. Specifically, this is manifested as the segmented temperature setting of the screw from the feed port to the die head, while the reaction residence time is controlled by the screw speed of the extruder.
[0034] The present invention also includes processes such as mixing, melt extrusion, cooling, pelletizing, and drying, all of which are conventional operations in the field and are not particularly required by the present invention.
[0035] The present invention also provides a method for preparing the low apparent density biodegradable thin film material described above.
[0036] Specifically, a method for preparing a low apparent density biodegradable thin film material includes the following steps:
[0037] Modified PBAT resin, calcium carbonate, coupling agent, and lubricant are thoroughly mixed, added to a twin-screw extruder, and sequentially melt-extruded, cooled, pelletized, and dried to obtain the final product.
[0038] Preferably, the screw speed of the twin-screw extruder is 100-700 rpm, for example 100, 200, 300, 400, 500, 600, or 700 rpm, more preferably 200-500 rpm, and the extrusion temperature is 130-190℃, for example 130, 140, 150, 160, 170, 180, or 190℃, more preferably 140-180℃.
[0039] In this invention, the low apparent density biodegradable film material is added to a blown film machine to produce a blown film product;
[0040] Preferably, the blown film temperature is 130-190℃, for example 130, 140, 150, 160, 170, 180, 190℃, and more preferably 140-180℃;
[0041] Preferably, a single-layer or multi-layer blown film machine is used.
[0042] The low apparent density biodegradable thin film material of this invention has an apparent density of 1.05 g / cm³. 3 The preferred values are 0.995-1.050 g / cm³. 3 It can be used in food packaging, logistics packaging and other fields.
[0043] Compared with the prior art, the present invention has the following technical advantages:
[0044] (1) The present invention designs the structure of PBAT. First, the PBAT resin is end-capped by an end-capping agent containing active groups. Then, acid monomers and acrylate monomers are introduced for copolymerization to change the regularity of the molecular chain segments and improve the mechanical properties of the material.
[0045] (2) Within the range of raw material ratios used in this invention, acid monomers can control the content of terminal carboxyl groups in modified PBAT, so that the terminal carboxyl groups react with calcium carbonate to produce tiny voids, resulting in a lower apparent density of the film without affecting the mechanical properties of the film, thus reducing costs. Detailed Implementation
[0046] The present invention will be further illustrated below with specific embodiments. These embodiments are merely illustrative and do not limit the scope of the invention.
[0047] The sources of the main raw materials used in the various embodiments and comparative examples of this invention are shown in Table 1 below. Unless otherwise specified, other raw materials and reagents were obtained through commercially available channels.
[0048] Table 1 Raw Materials and Sources
[0049]
[0050]
[0051] The performance test parameters and corresponding test methods of the PBAT thin film used in the embodiments and comparative examples of this invention are shown in Table 2 below:
[0052] Table 2 Performance Testing Methods
[0053] thickness micrometer GB / T 6672 Tensile strength g / 10min ISO 527 Elongation at break F / mN ISO 527 Apparent density % ISO 4593
[0054] The main processing equipment used in the embodiments and comparative examples of this invention is:
[0055] Twin-screw extruder, Coperion, model ZSK 26Mc 18, length-to-diameter ratio 52, screw diameter 26cm;
[0056] The blown film machine is from Zhejiang Zhuxin Machinery Co., Ltd., and its model number is SJ-35 600.
[0057] The main testing equipment and methods used in the embodiments and comparative examples of this invention are as follows:
[0058] Mahr thickness gauge, model C1208, from Germany;
[0059] The German ZWICK universal testing machine has a tensile testing rate of 500 mm / min.
[0060] Beijing Xuxin Instruments' fully automatic acid value analyzer, model ST-1514, measures acid value, i.e., the content of terminal carboxyl groups.
[0061] Example 1
[0062] (1) Preparation of end-capped PBAT
[0063] PBAT resin (T16, melt index 3g / 10min, weight average molecular weight 135,000, acid value 18.5mol / t) and glycidyl methacrylate were thoroughly mixed at a mass ratio of 100:0.5 and fed into a twin-screw extruder. The mixture was heated to melt and undergo an end-capping reaction. During the reaction, the screw speed was set at 220 rpm, and the screw temperature from the feed port to the die head was set in segments of 140℃, 140℃, 145℃, 145℃, 150℃, 155℃, 155℃, 160℃, 160℃, and 165℃. The extruded material was cooled in the extruder's water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain end-capped PBAT.
[0064] (2) Preparation of modified PBAT resin A
[0065] End-capped PBAT, methacrylic acid, methyl methacrylate, and dicumyl peroxide were thoroughly mixed at a mass ratio of 100:0.2:3.5:0.2 and fed into a twin-screw extruder. The mixture was heated to melt and polymerize. During the reaction, the screw speed was set to 100 rpm, and the screw temperature from the feed port to the die head was set in segments of 120℃, 120℃, 130℃, 135℃, 140℃, 145℃, 150℃, 150℃, 150℃, 150℃, and 145℃. The extruded material was cooled in the extruder's water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain modified PBAT resin A, with an acid value of 62 mol / t.
[0066] Example 2
[0067] (1) Preparation of end-capped PBAT resin
[0068] PBAT resin (T16, melt index 5 g / 10 min, weight average molecular weight 115,000, acid value 20.0 mol / t) and 2-vinyl-2-oxazoline were thoroughly mixed at a mass ratio of 100:1 and fed into a twin-screw extruder for end-capping reaction. The screw speed was set at 400 rpm during the reaction process, and the screw temperature from the feed port to the die head was set in segments of 145℃, 145℃, 145℃, 150℃, 150℃, 155℃, 155℃, 160℃, 160℃, 165℃, 165℃. The extruded material was cooled in the extruder water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain end-capped PBAT.
[0069] (2) Preparation of modified PBAT resin B
[0070] End-capped PBAT, methacrylic acid, methyl 2-(hydroxymethyl)acrylate, and dicumyl peroxide were thoroughly mixed at a mass ratio of 100:1:2.5:0.5 and fed into a twin-screw extruder. The mixture was heated and melted for polymerization. The screw speed was set at 300 rpm, and the screw temperature from the feed port to the die head was set in segments of 125℃, 125℃, 130℃, 135℃, 140℃, 145℃, 145℃, 145℃, 145℃, 145℃, 145℃. The extruded material was cooled in the extruder water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain modified PBAT resin B, with an acid value of 103 mol / t.
[0071] Example 3
[0072] (1) Preparation of end-capped PBAT resin
[0073] PBAT resin (T16, melt index 7 g / 10 min, weight average molecular weight 100,000, acid value 22.0 mol / t) and glycidyl methacrylate were thoroughly mixed at a mass ratio of 100:1.8 and fed into a twin-screw extruder. The mixture was heated to melt and undergo an end-capping reaction. During the reaction, the screw speed was set at 600 rpm, and the screw temperature from the feed port to the die head was set in segments of 150℃, 150℃, 155℃, 155℃, 160℃, 165℃, 170℃, 170℃, 180℃, 180℃, and 180℃. The extruded material was cooled in the extruder's water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain end-capped PBAT.
[0074] (2) Preparation of modified PBAT resin C
[0075] End-capped PBAT, maleic anhydride, methyl methacrylate, and benzoyl peroxide were thoroughly mixed at a mass ratio of 100:1.8:1.2:1 and fed into a twin-screw extruder. The mixture was heated to melt and polymerize. During the reaction, the screw speed was set at 450 rpm, and the screw temperature from the feed port to the die head was set in segments of 130℃, 130℃, 135℃, 135℃, 140℃, 145℃, 150℃, 150℃, 150℃, 150℃, 150℃. The extruded material was cooled in the extruder's water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain modified PBAT resin C, with an acid value of 148 mol / t.
[0076] Examples 4-6
[0077] Preparation of biodegradable thin film materials with low apparent density
[0078] The modified PBAT resin AC prepared in Examples 1-3 were thoroughly mixed with calcium carbonate, coupling agent, and lubricant. The mixture was then fed into a twin-screw extruder according to the raw material composition and dosage (by weight) in Table 3. The extrusion conditions were: screw speed 500 rpm, and screw temperatures from the feed port to the die head were set in segments of 140℃, 140℃, 140℃, 145℃, 145℃, 145℃, 155℃, 155℃, 165℃, 165℃, and 175℃. The extruded material was cooled in the extruder's water tank, pelletized, and dried in a vacuum oven at 90℃ for 4 hours to obtain a biodegradable film material.
[0079] The biodegradable thin film material was blown into a film at a blowing temperature of 170℃, and its performance was tested. The specific results are shown in Table 4.
[0080] Table 3. Raw materials and dosages in Examples 4-6 (S4-S6)
[0081]
[0082]
[0083] Comparative Example 1
[0084] Biodegradable film D1 was prepared according to the method in Example 5, except that: the modified PBAT resin B was directly replaced with commercially available PBAT (T16, melt index 5g / 10min, weight average molecular weight 115,000, terminal carboxyl content 20mol / t) before modification, and other operations and conditions remained unchanged. The results are shown in Table 4.
[0085] Comparative Example 2
[0086] Biodegradable film D2 was prepared according to the method in Example 6, except that commercially available PBAT (T16, melt index 5g / 10min, weight average molecular weight 115,000, acid value 50mol / t) was used to replace the modified PBAT resin C, while other operations and conditions remained unchanged. The results are shown in Table 4.
[0087] Comparative Example 3
[0088] The modified PBAT resin was prepared according to the method of Example 2, except that step (1) was omitted and in step (2) PBAT resin (T16, melt index 5g / 10min, weight average molecular weight 115,000, acid value 20) was directly used to replace the end-capped PBAT. Other operations and conditions remained unchanged. The results are shown in Table 4.
[0089] The modified PBAT resin B was replaced with the modified PBAT resin described above, and the biodegradable film D3 was prepared according to the method in Example 5. The results are shown in Table 4.
[0090] Comparative Example 4
[0091] Modified PBAT resin was prepared according to the method in Example 2, except that methacrylic acid monomer was not added in step (2), and other operations and conditions remained unchanged. The results are shown in Table 4.
[0092] The modified PBAT resin B was replaced with the modified PBAT resin described above, and the biodegradable film D4 was prepared according to the method in Example 5. The results are shown in Table 4.
[0093] Comparative Example 5
[0094] Modified PBAT resin was prepared according to the method in Example 2, except that 2-(hydroxymethyl)acrylate monomer was not added in step (2), and other operations and conditions remained unchanged. The results are shown in Table 4.
[0095] The modified PBAT resin B was replaced with the modified PBAT resin described above, and the biodegradable film D5 was prepared according to the method in Example 5. The results are shown in Table 4.
[0096] Comparative Example 6
[0097] Modified PBAT resin was prepared according to the method in Example 2, except that methyl 2-(hydroxymethyl)acrylate was replaced with vinyl acetate in step (2), while other operations and conditions remained unchanged. The results are shown in Table 4.
[0098] The modified PBAT resin B was replaced with the modified PBAT resin described above, and biodegradable film D6 was prepared according to the method in Example 5. The results are shown in Table 4.
[0099] Table 4. Performance test results of products in Examples 4-6 (S4-S6) and Comparative Examples 1-6 (D1-D6)
[0100]
[0101] As can be seen from Comparative Examples 1-6 and Examples 4-6, the films prepared using the modified PBAT resin of the present invention have excellent mechanical properties and lower apparent density.
[0102] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and additions without departing from the method of the present invention, and these improvements and additions should also be considered within the scope of protection of the present invention.
Claims
1. A low apparent density biodegradable thin film material, characterized in that, It comprises the following components, in parts by weight: 65-80 parts of modified PBAT resin, 20-35 parts calcium carbonate 0.1-1 part coupling agent, Lubricant 0.1-1 part; The modified PBAT resin is prepared by end-capping PBAT resin with an end-capping agent and then copolymerizing it with acid monomers and acrylate monomers. The modified PBAT resin has a terminal carboxyl group content of 50-150 mol / t.
2. The low apparent density biodegradable thin film material according to claim 1, characterized in that, It comprises the following components, in parts by weight: 67-77 parts of modified PBAT resin, Calcium carbonate 23-33 parts, 0.3-0.8 parts of coupling agent, Lubricant 0.3-0.8 parts.
3. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The PBAT resin has a melt index of 2-8 g / 10 min at 190°C and 2.16 kg.
4. The low apparent density biodegradable thin film material according to claim 3, characterized in that, The PBAT resin has a melt index of 4-7 g / 10 min at 190°C and 2.16 kg.
5. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The PBAT resin has a weight-average molecular weight of 90,000 to 150,000.
6. The low apparent density biodegradable thin film material according to claim 5, characterized in that, The weight-average molecular weight of the PBAT resin is 100,000 to 140,000.
7. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The PBAT resin has a terminal carboxyl group content of 5-25 mol / t.
8. The low apparent density biodegradable thin film material according to claim 7, characterized in that, The PBAT resin has a terminal carboxyl group content of 10-24 mol / t.
9. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The capping agent is a capping agent containing an active group, wherein the active group is selected from epoxy groups and / or oxazoline groups; and / or The acid monomers are selected from one or more of acid anhydride monomers and carboxylic acid monomers; and / or The acrylate monomers are one or more of methyl methacrylate, ethyl methacrylate, and 2-(hydroxymethyl) methacrylate.
10. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The end-capping agent is selected from vinyl end-capping agents.
11. The low apparent density biodegradable thin film material according to claim 9 or 10, characterized in that, The capping agent is selected from one or more of vinyloxazoline capping agents and vinyl epoxy capping agents.
12. The low apparent density biodegradable thin film material according to claim 11, characterized in that, The capping agent is selected from one or more of 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, and glycidyl methacrylate.
13. The low apparent density biodegradable thin film material according to claim 9, characterized in that, The acid monomers are selected from one or more of maleic anhydride, methacrylic acid, and 2,3-diphenylmaleic anhydride.
14. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The calcium carbonate has a mesh size of 800-10000 mesh; and / or The coupling agent is selected from one or more of silane coupling agents and titanate coupling agents; and / or The lubricant is selected from one or more of erucamide, oleamide, and ethylene bis-stearamide.
15. The low apparent density biodegradable thin film material according to claim 14, characterized in that, The calcium carbonate has a mesh size of 2000-8000 mesh.
16. The low apparent density biodegradable thin film material according to claim 14, characterized in that, The coupling agent is selected from one or more of γ-aminopropyltriethoxysilane, γ-chloropropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-(methacryloyloxy)propyltrimethoxysilane.
17. The low apparent density biodegradable thin film material according to claim 1, characterized in that, The modified PBAT resin is prepared by the following method, including the following steps: (1) Mix PBAT resin and end-capping agent thoroughly, add to an extruder, heat to carry out end-capping reaction, melt extrusion, cool, pelletize, and dry to obtain end-capped PBAT; (2) The end-capped PBAT, acid monomers, acrylate monomers and initiator are thoroughly mixed and added to an extruder. The mixture is heated to carry out the polymerization reaction. After melt extrusion, cooling, pelletizing and drying, the modified PBAT resin is obtained.
18. The low apparent density biodegradable thin film material according to claim 17, characterized in that, In step (1), the mass ratio of PBAT resin to end-capping agent is 100:(0.1-2).
19. The low apparent density biodegradable thin film material according to claim 18, characterized in that, The mass ratio of PBAT resin to end-capping agent is 100:(0.3-1.8).
20. The low apparent density biodegradable thin film material according to claim 17, characterized in that, The initiator in step (2) is selected from one or more of dicumyl peroxide, benzoyl peroxide, and methyl ethyl ketone peroxide; and / or In step (2), the mass ratio of the capped PBAT to the acid monomer, acrylate monomer, and initiator is 100:(0.1-2):(1-4):(0.1-1.2).
21. The low apparent density biodegradable thin film material according to claim 20, characterized in that, The mass ratio of the capped PBAT to the acid monomer, acrylate monomer, and initiator is 100:(0.3-1.8):(1.5-3.5):(0.2-1).
22. The low apparent density biodegradable thin film material according to claim 17, characterized in that, The end-capping reaction in step (1) involves controlling the extruder temperature to 140-180℃; and / or In step (2), the polymerization reaction is carried out by controlling the extruder temperature to 120-150℃.
23. The low apparent density biodegradable thin film material according to claim 22, characterized in that, The end-capping reaction is carried out by controlling the extruder temperature at 145-175℃.
24. The low apparent density biodegradable thin film material according to claim 22, characterized in that, The polymerization reaction is carried out with the extruder temperature controlled at 125-145℃.
25. The low apparent density biodegradable thin film material according to claim 17, characterized in that, In step (1), the end-capping reaction is performed with an extruder screw speed of 100-700 rpm.
26. The low apparent density biodegradable thin film material according to claim 25, characterized in that, The end-capping reaction is performed with an extruder screw speed of 200-600 rpm.
27. The low apparent density biodegradable thin film material according to claim 17, characterized in that, In step (2), the extruder screw speed for the polymerization reaction is 50-500 rpm.
28. The low apparent density biodegradable thin film material according to claim 27, characterized in that, The polymerization reaction is carried out at an extruder screw speed of 100-400 rpm.
29. A method for preparing a low apparent density biodegradable thin film material according to any one of claims 1-28, characterized in that, Includes the following steps: Modified PBAT resin, calcium carbonate, coupling agent, and lubricant are thoroughly mixed, added to a twin-screw extruder, and then melt-extruded, cooled, pelletized, and dried to obtain the final product.
30. The preparation method according to claim 29, characterized in that, The twin-screw extruder has a screw speed of 100-700 rpm and an extrusion temperature of 130-190℃.
31. The preparation method according to claim 30, characterized in that, The twin-screw extruder has a screw speed of 200-500 rpm and an extrusion temperature of 140-180℃.
Citation Information
Patent Citations
Base resin of blow-moulded degradable film and blow-moulded degradable film
CN110283438A
Biodegradable foaming sheet and preparation method thereof
CN108559234A
Calcium carbonate filled PBAT / PLA degradable film and preparation method thereof
CN113652063A